Regio- and Stereoselective Approach to 1,4-Ditertiary Carbinols from Dimethyl Tartrate - Budragchaa, Tuvshinjargal; Roller, Alexander; Widhalm, Michael (Synthesis, 2012)
A rational strategy for accessing tetrahydroxy compounds in predictable stereoselective fashion from di-O-benzyl protected tartrate is presented. Up to four different aromatic, aliphatic, and vinyl substituents could be stepwise introduced at C1 and C4. This is exemplified in an economic preparation of eight dihydroxy compounds from natural tartaric acid in six steps and 19–59% overall yield. A final deprotection step afforded the corresponding tetrahydroxy compounds in good yields.
Keywords: regioselectivity; diastereoselectivity; diols; nucleophilic addition; Grignard reaction